Administration Staff’s Descriptions of Inclusion in Finnish Vocational Education and Training - Ryökkynen, Sanna; Raudasoja, Anu; Heino, Sanna; Maetoloa, Katja; Pynnönen, Päivi (Nordic Journal of Comparative and International Education (NJCIE), 2022)
Inclusion is understood in various ways in research, in documents guiding educational practices, and in stakeholders’ speeches. This study contributes to the European discussion on the ambiguity of inclusion by investigating the descriptions of Finnish vocational education and training (VET) administration personnel both at the national and vocational institution levels. It gives light on the interconnections between participants’ and Finnish and EU-level interpretations of inclusion in VET. We ask how the representatives of national educational administration and vocational institutions’ administration describe inclusion. The data was collected in the spring of 2021 by interviewing representatives (N=18) of national educational administration and vocational institution administration. We used Qvortrup and Qvortrup’s (2018) definition of inclusion as our theoretical lens. The participants’ descriptions of inclusion were constructed by portraying the significance of students’ equity, equality, participation, accessibility, special support and belonging in the VET community at the numeric level but they lack consideration of students’ activity in those communities and students’ own experiences. The participants did not address the relevance of different social arenas of inclusion or exclusion in their descriptions, but they described VET colleges as one social system. Moreover, the participants did not reflect on the degree of being included or excluded. Their perspectives were constructed through the Finnish VET context, and they created a strong promise of education, which would provide equal opportunities for all to study and acquire competence according to the qualification requirements in VET. Their approaches were based rather on the identification of special needs students and their needs than on considerations for social cohesion, active citizenship and lifelong learning. This fostered the invitation for the Finnish Ministry of Education and Culture and the National Board of Education to define inclusion more precisely in VET so that the education providers would have an explicit framework and goals to advance inclusion in practice.